1998
DOI: 10.1099/00221287-144-12-3463
|View full text |Cite
|
Sign up to set email alerts
|

Cell integrity and morphogenesis in a budding yeast septin mutant

Abstract: The non-sporulating diploid strain V327 of Saccharomyces cerevisiae was previously isolated in a search for thermosensitive autolytic mutants. This strain is very efficient a t releasing intracellular proteins into the medium when incubated a t high temperatures. The expression of this lytic phenotype depends on a morphogenetic defect, consisting of the appearance of elongated chains of cells. Transmission electron microscopy revealed a mislocalization of septa at semi-permissive temperatures and a total lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…The septation defects observed in the present study are also similar to those seen in S. cerevisiae mutants with mislocalized septins (14,(44)(45)(46). The S. cerevisiae septation apparatus, which includes septins and chitin synthase, can function autonomously at ectopic locations independently of cell division (14).…”
Section: Figsupporting
confidence: 86%
“…The septation defects observed in the present study are also similar to those seen in S. cerevisiae mutants with mislocalized septins (14,(44)(45)(46). The S. cerevisiae septation apparatus, which includes septins and chitin synthase, can function autonomously at ectopic locations independently of cell division (14).…”
Section: Figsupporting
confidence: 86%
“…39 We have previously discussed possible examples for distinct alleles/isoforms of a and b tubulins. 15 Additionally, a recent study investigating "assembly control" exerted by chaperones resident in the ER on the ab heterodimer of the T cell receptor (TCR) concluded that folding of the a and b subunits is dimerization-dependent, leading chaperones to sequester nascent a and b polypeptides until they have achieved native folds in the context of the ab heterodimer, which is linked irreversibly together by disulfide bonds.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, septin mutant cells have strikingly similar phenotypes to those induced by ENTH2 overexpression (Fig. 1B-D), including chains of cells with aberrant septum formation (Versele and Thorner, 2004;Schmidt et al, 2003;Roh et al, 2002;Cid et al, 1998). Therefore, we asked whether septin assembly is affected by the ENTH2-specific dominant-negative effect.…”
Section: Enth2 Dominant-negative Effect Leads To Aberrant Septin Strumentioning
confidence: 90%
“…Interestingly, some of these mutants have been reported to interact poorly with the septin-organizing protein Bem3 (Richman and Johnson, 2000). Furthermore, septin deficiencies produced phenotypes very similar to those observed upon ENTH2 overexpression, including elongated, chained buds and aberrant septa (Versele and Thorner, 2004;Schmidt et al, 2003;Roh et al, 2002;Cid et al, 1998).…”
Section: Journal Of Cell Science 122 (14)mentioning
confidence: 93%